Identification of interaction mechanisms during drag finishing by means of an original macroscopic numerical model. (September 2021) - Malkorra, Irati; Souli, Hanène; Claudin, Christophe; Salvatore, Ferdinando; Arrazola, Pedro; Rech, Joel; Seux, Hervé; Mathis, Aude; Rolet, Jason
Abstract: Drag finishing is one of the mass finishing processes that enhances surface roughness on complex parts due to the mechanical action of abrasive media. Due to the complexity of the process, industrial practice is based on experience. This paper proposes a model simulating abrasive media flowing around a part during a drag finishing operation at a macroscopic scale. The 2D model is based on an Arbitrary Lagrangian Eulerian (ALE) formulation that provides relevant mechanical parameters such as the distribution of stresses (normal and shear stresses) and sliding velocities between abrasive media and the surface to be polished. Abrasive media are modelled as a continuous material with a Drucker-Prager plastic constitutive equation. This last has been calibrated as a result of triaxial testing, commonly used to characterise soils in civil engineering. Two abrasive media (spherical and pyramidal shape) having the same composition were characterised. Pyramidal media exhibit significantly higher rheological behaviour compared to spherical one. The model is shown to be very sensitive to the media's rheological behaviour but also to the immersion depth. Pyramidal media leads to much higher normal and shear stresses, which are even higher at deeper immersion depths. Drag finishing experimental tests were carried out to evaluate the efficiency of the model. The correlation between experimental drag finishing tests and numerical test results reveals the physical mechanisms at the interface between media and the surface. Spherical media, with a small/orthogonal orientation impact angle, promotes plastic deformation, while the main mechanisms becomes cutting at higher impact angles. However, pyramidal media promotes cutting irrespective of the orientation angle. Moreover, it was concluded that the optimal mechanical loading combination happens between 30 and 60° for both medias, as the shearing energy reaches its maximum value. Graphical abstract: Image 1 Highlights: An original 2D Arbitrary Lagrangian Eulerian (ALE) model simulates abrasive media flow around the part in drag finishing. Triaxial tests employed to characterise the rheological properties of abrasive media. ALE model predicts local physical parameters (normal + shear stress, velocity) induced by media around the part. Experimental Sa is correlated with the local physical properties extracted from the ALE model. The paper provides physical parameters to explain the dominant role of abrasive media shape and surface orientation angle.